2 Developing a new model to investigate the mechanobiology of primary blast in soft tissue. Issue 2 (23rd March 2023) - Staruch, RMT; Sedman, A; Macildowie, S; Cork, L; Cleveland, RO; Snelling, S; Thompson, M; Rickard, RF; Spear, AM
Abstract : Introduction: Efforts to understand the pathology resulting for explosions, such as terrorist bombings or industrial accidents, are increasingly focused on connecting biophysical stimuli with cell fate, widely referred to as mechanobiology. This work presents a novel mechanobiologically relevant biomimetic in vitro 3D muscle model of blast injury together with a custom shock tube designed to deliver relevant explosive loading to cell culture together with analysis of the high throughput whole genome RNA sequencing detailing the effect of explosive shock waves on cell culture over time Method: Immortalised mouse skeletal muscle cells were encapsulated in fibrin hydrogels and cast between custom-made 3D printed flexible posts. Custom silicone tissue culture plates were designed and fabricated to enable the exposure of cultured skeletal muscle hydrogels (SkmH) to live explosive shock waves. In brief, a frustum shock tube (FST) facility was designed and built at Dstl to delivery relevant loading to a standard tissue culture well plate. A three-arm explosive trial utilising SkmH was then conducted. After exposure SkmHs were evaluated at 1 hour, 1 day, 3 day and 7 days post blast for cell metabolic activity (presto blue assay), and stored for subsequent gene expression analysis (RNA later solution), imaging (fixation in 4% paraformaldehyde then PBS) and serum contents (media frozen & stored). Results: SkmHs cultured between 3D printed posts demonstrated aligned morphology, expressed markers consistent with myotube formation and contractile properties from post deflection. SkmHs exposed to explosive blast demonstrated dose-dependent metabolic changes. Conclusion: This work outlines the design and development of a mechanosensitive apparatus for probing the cellular effects of blast shock wave on biomimetic tissue culture models. Metabolic data up to one week after exposure gives new and detailed insight into the cellular signalling after blast in skeletal muscle.